Analisis penilaian kinerja organisasi dengan menggunakan konsep balanced scorecard pada perusahaan daerah air minum (pdam) payakumbuh - Suci Mardatillah; Azwir Nasir; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to do and see an overview of the organization's overall performance assessment using the concept of Balanced Scorecard on Regional Water Company (PDAM) Payakumbuh, as seen from four perspectives: financial perspective, customer perspective, internal business perspective, and learning and growth perspective .The method used is the method of survey research deskriptif approach. Obtained from data collected secondary data from company financial data and reports. In addition, through the distribution of questionnaires to the 39 existing employees at the Regional Water Company (PDAM) Payakumbuh. Processing and analyzing the data using the classical assumption test after test the validity, reliability, and data analysis.From the results of research on the measurement of company performance using the Balanced Scorecard concept , the importance of performance measurement results can be said to be good financial perspective , ie from the ROI , the Current Ratio , Profit Margin , Operating Ratio . Results of performance measurement of the level of customer perspective customer acquisition , customer retention , customer profitability , and customer satisfaction levels also showed a good performance . The results of measurements of internal business perspective , namely innovation and after-sales service company , the overall performance of the company has shown good results . The measurement results of learning and growth perspective , the employee productivity and employee retention can be said enough . While the level of employee satisfaction also showed good results . While the validity of the test results on the level of employee satisfaction can be concluded that the measurement of the five characteristics , namely ( 1 ) the policy of the company, ( 2 ) motivation to work , ( 3 ) access to information and communication , ( 4 ) the physical condition of the company , and ( 5 ) work load and salaries , showed valid results . While testing the reliability test results also showed results quite reliable .Keywords : Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business, Learning and Growth Perspective.